Interspecific and intraspecific phenotypic diversity for drought adaptation in bioenergy Arundo species. Issue 4 (16th February 2021) - Faralli, Michele; Williams, Kevin; Corke, Fiona; Li, Mingai; Doonan, John H.; Varotto, Claudio
Abstract: Biomass crops are commonly grown in low‐grade land and selection of drought‐tolerant accessions is of major importance to sustain productivity. In this work, we assess phenotypic variation under different environmental scenarios in a series of accessions of Arundo donax, and contrast it with two closely related species, Arundo donaciformis and Arundo plinii . Gas‐exchange and stomatal anatomy analysis showed an elevated photosynthetic capacity in A . plinii compared to A. donax and A. donaciformis with a significant intraspecific variation in A. donax . The three species showed significantly contrasting behaviour of transpiration under developing water stress and increasing vapour pressure deficit (VPD), with A. donax being the most conservative while A . plinii showed an elevated degree of insensitivity to environmental cues. Under optimal conditions, A. donax had the highest estimated leaf area (projected leaf area) and plant dry weight although a significant reduction under water stress was observed for A. donax and A. donaciformis accessions while no differences were recorded for A . plinii between optimal growing conditions (well‐watered [WW]) and reduced soil water availability (water‐stressed [WS]). A. donax displayed a markedly conservative water use behaviour but elevated sensitivity of biomass accumulation under stress conditions. By contrast, in A . plinii, biomass and transpiration were largely insensitive to WS and increasing VPD, though biomass dry weight under optimal conditions was significantly lower than A. donax . We provide evidence of interspecific phenotypic variation within the Arundo genus while the intraspecific phenotypic plasticity may be exploited for further selection of superior clones under disadvantageous environmental conditions. The extensive trade‐off between water use and biomass accumulation present in the three species under stress conditions provides a series of novel traits to be exploited in the selection of superior clones adapted to different environmental scenarios. Non‐destructive approaches are provided to screen large populations for water‐stress‐tolerant A. donax clones. Abstract : We compared by high‐throughput phenotyping natural populations of three species of the Arundo genus, the giant reed Arundo donax and two of its wild relatives, Arundo donaciformis and Arundo plinii, for drought tolerance. A clearly water‐conservative behavior was observed in A. donax and A. donaciformis . Conversely, A . plinii displayed an overall non‐conservative response to developing water stress. The intraspecific variation we uncovered in A. donax suggests the possibility of selecting natural ecotypes for agronomic use with superior combinations of preferable traits for different environments. In addition, our work stresses the importance of non‐destructive phenotyping approaches for plant‐environment interaction studies.